Social Cognition in Borderline Personality Disorder: Evidence for Disturbed Recognition of the Emotions, Thoughts, and Intentions of others - Preißler, Sandra; Dziobek, Isabel; Ritter, Kathrin; Heekeren, Hauke R.; Roepke, Stefan (Frontiers in Behavioral Neuroscience, 2010)
Disturbed relatedness is a core feature of borderline personality disorder (BPD), and impaired social cognition or deficits in “mentalization” are hypothesized to underlie this feature. To date, only weak empirical evidence argues for impairment in the recognition of emotions, thoughts, or intentions in BPD. Data from facial emotion recognition research indicate that these abilities are altered in BPD only if tasks are complex. The present study aims to assess social cognitive abilities in BPD. Sixty-four women with BPD and 38 healthy controls watched the “Movie for the Assessment of Social Cognition” (MASC), a newly developed film displaying social interactions, and asking for an assessment of the intentions, emotions, and thoughts of the characters. In addition, participants completed an established but less ecologically valid measure of social cognition (“Reading the Mind in the Eyes”; RME). In the RME task, BPD patients did not display impairment in social cognition compared to healthy controls. By contrast, on the more sensitive MASC, women with BPD showed significantly impaired abilities in social cognition compared to healthy controls in their recognition of emotions, thoughts, and intentions. Comorbid PTSD, intrusions, and sexual trauma negatively predicted social cognitive abilities on the more sensitive MASC. Thus, our results suggest impaired social cognitive abilities in BPD. Especially for comorbid PTSD, intrusive symptoms and history of sexual trauma predicted poor outcomes on social cognition tasks.